On Canada's frontier [electronic resource] : sketches of history, sport, and adventure and of the Indians, missionaries, fur-traders, and newer settlers of western Canada - Ralph, Julian, 1853-1903 (London : J.R. Osgood, 1892)
Electronic reproduction. Mode of access: Internet. 44